Different depositing amount of CuInS2 on TiO2 nanoarrays for polymer/CuInS2–TiO2 solar cells. (December 2015) - Yue, Wenjin; Pan, Yuwen; Xie, Zhongwen; Yang, Xing; Hu, Lingling; Hong, Lirui; Tong, Yafei; Cheng, Qingqing
Abstract: This paper reports the deposition of CuInS2 on TiO2 nanoarrays, with different depositing amounts and demonstrates the application of TiO2 –CuInS2 composites in polymer-based solar cells. The composites of TiO2 –CIS1 and TiO2 –CIS2 were prepared by the deposition of CuInS2 on TiO2 with one-step or two-step solvethermal reactions, respectively, and characterized by XRD, SEM, TEM, absorption spectrum and PL spectrum. Results showed that TiO2 –CIS1 displayed the higher light-harvesting ability and PL quenching efficiency compared to TiO2 –CIS2, although less CuInS2 was deposited on TiO2 surface. As a result, polymer/TiO2 –CIS1 solar cells displayed much higher J sc correlated with the increased absorptivity and charge separation efficiency, and the higher V oc was originated from the presence of strong interaction between TiO2 and CuInS2 in TiO2 –CIS1 resulting in the effective modification of TiO2 surface by CuInS2 .